Thematic Analysis and its Interdisciplinary Interest:: Advantage or a Disadvantage for Holton’s Purpose? - Alahou, Georges (Conatus - Journal of Philosophy, 2023)
The term “thematic analysis” abounds in research articles and appears in the titles of books, without the authors of these writings being primarily concerned with defining what thematic analysis is. Thematic analysis is present in the current vocabulary of several disciplines and is presented as a working method of choice in psychology, sociology, or linguistics, to name but a few. This article seeks to situate thematic analysis in the thinking of Holton Gerald, who introduced it into the philosophy of science as a rational approach that can account for scientific discovery and progress. The aim of this article is to see whether the attested interdisciplinary interest nature of thematic analysis argues in favour or against Holton’s claim of making it a credible and acceptable tool in philosophy of science.